Betrayed by Work - Erickson, Julia; Vosburg, Suzanne (Ascent Audio, 2021)
Emotionally, getting fired is one of life's most difficult experiences. When women get fired, it is often devastating, traumatic, and isolating. We experience a sudden powerlessness that can destroy our confidence and feelings of self-worth. We grieve. We feel broken. It affects our self-esteem, our financial well-being, our professional identity, and our ability to look for other work-in short, it affects our entire way of life. How, then, does a woman navigate the emotional impact of this event? With other women. You are not alone. In Betrayed by Work, authors Julia Erickson, MBA, and Suzanne Vosburg, PhD, bear witness to the stories of women just like you-and just like them. This book shows how women lost their jobs, describes what happened to them immediately and in the aftermath, validates women's feelings about being fired, and offers a source of hope and companionship to those of us coping with either our own job loss or the sudden job loss of someone we know or love. In listening to this book, discover: true stories from women who are honest about how they were fired and what they felt while being let go; key points to help process each story and apply its lesson to your own experience; and practical takeaways and suggestions to help you cope in the immediate aftermath of your job loss.